Do regional price levels converge? Paneleconometric evidence based on German districts - Christian Dreger; Reinhold Kosfeld (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
We investigate price index convergence on the base of regional data for 439 German districts. Prices refer to the overall consumer price index as well as to the index without housing prices. To increase the efficiency of the testing framework, a panel unit root analysis is performed, where cross section dependencies are taken into account. The tests indicate a lack of regional price convergence. While the idiosyncratic component of price differentials is mostly stationary, their common component is driven by a unit root. The results are very similar for the overall price index and the index without housing prices, and for the Western and Eastern part of the German economy. Obviously the elimination of housing prices is not sufficient to obtain a price index where tradable products dominate. One rationale of our findings is the persistent west-east divide in consumer prices. A second argument is related to the persistence of the price gradient between urban and rural regions.
Keywords: E31; R10; C33; 330; Regional price differentials; price convergence; panel unit roots; Regionale Preisstruktur; Lebenshaltungsindex; Inflationskonvergenz; Deutschland; Neue Bundesländer; Alte Bundesländer